Application of Molecular Typing Methods for Analysis of Strains of Rickettsiae of the Spotted Fever Group and Rabies Virus - S. N. Shpynov; E. M. Poleshchuk; N. V. Rudakov; I. E. Samoilenko; T. A. Reshetnikova; L. V. Kumpan; A. N. Kolomeets; G. N. Sidorov; S. E. Tkachev; S. V. Gribencha (Проблемы особо опасных инфекций, 2012)
50 strains of spotted fever group (SFG) rickettsiae and 36 lyssaviruses strains from the collection of Omsk Research Institute of Natural Focus Infections were identified and typed using the approaches of molecular biology, epidemiology and bioinformatics. The taxonomic status of the studied cultures of SFG rickettsiae was identified. Zonation of the Russian Federation territories according to the spread of SFG pathogenic rickettsiae in their hosts - ixodic ticks was carried out. Lyssaviruses distribution in the territory of Siberia was considered.